The fluctuation of school-based management implementation - Aan Komariah, Hadiyanto, (Opción, 2019)
The main goal of this study is to evaluate policy and implementation of school-based management in Junior Secondary Schools in some cities based on studies of qualitative and quantitative approaches carried out in the Directorate of Junior Secondary Schools, the Ministry of Education and Culture, Junior Secondary Schools in Banten and Padang Indonesia. As a result, at a national level, the Central Government has made regulations concerning school-based management and has provided funds that allow schools to implement SBM. In conclusion, the successful implementation of school-based management principles is supported by accountability, transparency, partnership, community participation, and education autonomy.